Are medication-induced salivary changes the culprit of osteonecrosis of the jaw? A systematic review - Suryani, Isti Rahayu; Ahmadzai, Iraj; That, Minh Ton; Shujaat, Sohaib; Jacobs, Reinhilde (Frontiers in Medicine, 2023)
Purpose: This systematic review was performed to assess the potential influence of medication-induced salivary changes on the development of medication-related osteonecrosis of the jaw (MRONJ).Methods: An electronic search was conducted using PubMed, Web of Science, Cochrane and Embase for articles published up to June 2023. Risk of bias assessment was performed according to the modified Newcastle-Ottawa Scale (NOS). Due to heterogeneity of the selected studies in relation to type of medications and outcomes evaluated, a meta-analysis could not be performed.The initial search revealed 765 studies. Only 10 articles were found to be eligible based on the inclusion criteria that reported on the impact of salivary changes on MRONJ following administration of different medications. A total of 272 cases of MRONJ were included (35% female, 32% male, 32% no gender reported) with a mean age of 66 years at the time of diagnosis. Patients administered with bisphosphonates, steroids, chemotherapy, thalidomide, interferon and hormone therapy had a significantly higher association between decreased salivary flow and MRONJ occurrence. In addition, bisphosphonates, denosumab, and other bone modifying agents showed a significantly higher risk of developing MRONJ owing to the changes in salivary microbiome profile, cytokine profile, interleukin, hypotaurine, and binding proteins.The reduction in salivary flow and changes in the concentration of salivary proteins were associated with the development of MRONJ. However, due to the availability of limited evidence, the findings of the review should be interpreted with caution.